Female migration from peasant communities: A case study, Cusco - Radcliffe, Sarah (1985)
Currently, various political and economic aspects of the economic crisis that Peru is going through have led to a new approach that sees the mountains as a possible place for new development. This topic is based, to a large extent, on an incomplete analysis of the nature of the economy and society in the mountains, despite the fact that much valuable work has recently been done in the fields of sociology, anthropology and economics. One aspect of the development of the sierra and, indeed, an indicator of its current crisis, has to do with rural-urban migration from the small towns and mountain communities to the coast, especially to Lima.